High-energy ball milling for high productivity of nanobiochar from oil palm biomass - Ng, Lawrence Yee Foong; Ariffin, Hidayah; Tengku Yasim Anuar, Tengku Arisyah; Ahmad Farid, Mohammed Abdillah; Hassan, Mohd Ali (Multidisciplinary Digital Publishing Institute, 2022)
The current production method of nanobiochar (NBC), an emerging, environmentally friendly nanocarbon material, is tedious and lengthy. Therefore, in this study we aimed to improve the productivity of NBC via high-energy ball milling by manipulating the grinding media and processing time. The particle size distribution of the resulting NBC measured using dynamic light scattering showed that grinding media with steel balls of different sizes were more effective at producing NBC than small uniform steel balls, which failed to produce NBC even after 90 min of milling. Average NBC particles of around 95 nm were achieved after only 30 min of ball milling, and the size was further reduced to about 30 nm when the milling was prolonged to 150 min. Further prolonging the milling duration led to agglomeration, which increased the size of the biochar nanoparticles. The thermogravimetric analysis (TGA) data showed that the duration of milling and particle size did not cause noticeable differences in the thermal stability of the NBC. Based on the FTIR analysis, the chemical structure of the NBC was not affected by the ball milling. The results showed that 60 min of high-energy ball milling is sufficient to produce NBC particles of 75 nm, with a large surface area and high thermal stability. This could prove beneficial in a myriad of applications, ranging from agriculture to composite fabrication.